(untitled) (Heritage, 2023)
The research was conducted with the aim of determining the degree and quality of the connection between judo techniques and motor skills defined as manifest and latent dimensions. Therefore, 237 male respondents aged 11 to 12 years were tested. This sample can be considered representative of judokas of the same age. 20 motor tests were used to assess motor skills. They were chosen for the structural analysis to be performed at the level of second-order factors according to the structural model. For the evaluation of the technical competence of judokas, 7 representatives of certain major groups of techniques were taken. The groups of judo techniques are taken to cover: hand techniques, side techniques, leg techniques, sacrifice techniques, ground hold techniques, chokes and leverage techniques. All variables used in previous research were subjected to thorough validation. Canonical analysis of latent motor dimensions and judo techniques indicated a significant correlation. However, apart from the fact that this method is currently considered the optimal research procedure, numerous further researches are needed that would continuously supplement knowledge about the methods and laws of the relationship between motor skills and judo techniques